The motivation and consequence of fact-checking behavior: An experimental study - Valeria Bodishtianu; Dongfang Gaozhao; Pengfei Zhang (PLoS ONE, 2025)
In a series of online experiments, we asked people to evaluate news veracity and varied two experimental conditions: (1) the opportunity to receive fact-checking results and (2) bonus payment for accuracy. We tested three competing theories for fact-checking behavior: value of information (VoI), limited attention (LA), and motivated reasoning (MR). We find that monetary incentives do not promote fact-checking. Prior awareness of the news and perceived easiness in determining news authenticity significantly reduce fact-checking. Democrats are more likely to fact-check on the news aligning with Republicans’ ideology, suggesting a tendency to seek information when there is a need to defend one’s pre-existing belief. Overall, our results contradict VoI, show mixed evidence for MR, and support LA. When available, fact-checking consistently improves subjects’ accuracy in evaluating news veracity by over 40%, underscoring the importance of promoting fact-checking in curbing misinformation.